Avoiding extinction: the importance of protecting isolated Indigenous tribes. (March 2021) - Ortiz-Prado, Esteban; Cevallos-Sierra, Gabriel; Vasconez, Eduardo; Lister, Alex; Pichilingue Ramos, Eduardo
Isolated Indigenous peoples are a group of Indigenous tribes that live in voluntary isolation in remote and mostly inaccessible territories. Together with Indigenous peoples in initial contact, Isolated Indigenous peoples are threatened continuously by advancing extractive activities, the absence of public policies and protection measures by the State, and the pressure of illegal activities on their territories. Generating multidimensional public policies that protect these groups is essential. This commentary shares South America's perspective on the matter as it is the region where most of the isolated groups reside.